Conservation of the 5S-bearing chromosome pair and co-localization with major rDNA clusters in five species of Astyanax (Pisces, Characidae) - Almeida-Toledo, L. F.; Ozouf-Costaz, C.; Foresti, F.; Bonillo, C.; Porto-Foresti, F.; Daniel-Silva, MFZ (Karger, 2002)
Major and 5S ribosomal genes have been localized in chromosomes from five fish species, genus Aslyanax, using in situ hybridization (FISH) with 28S and 5S rDNA probes. In situ signals for the major rDNA co-localized with the 5S rDNA clusters in the pericentromeric region of one marker chromosome in all five species analyzed. The conserved localization of these two rDNA clusters in the five related Astyanax species was considered as indicative of a close relationship among them. The use of these molecular markers for elucidating evolutionary relationships among closely related taxa is discussed. Copyright (C) 2002 S. Karger AG, Basel.